Silas W. Browning papers - Browning, Silas W., 1820-1888.
Chiefly letters (1862-1863) from Browning during his service in the 53rd Massachusetts Volunteer Infantry to his wife and daughters from Mississippi and Louisiana relating to his activities as a hospital steward, the diet and the health of the regiment, conduct of the troops, and conditions in the South during the Civil War.
Abolitionist and soldier.
Collection material in English.
Keywords: Browning family; United States. -- Army -- Military life; United States. -- Army. -- Massachusetts Infantry Regiment, 53rd (1862-1863); Abolitionists; Louisiana -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Medical care; United States -- History -- Civil War, 1861-1865 -- Personal narratives; Abolitionists; Soldiers